A functional model of social loafing: when and how does social loafing enhance job performance? - Liu, Xin (Journal of business ethics, 2024)
Many previous studies have documented the detrimental effects of social loafing on others (interpersonal impacts) at the between-person level. However, social loafing may carry underappreciated intrapersonal functional effects at the within-person level. Our research develops a novel theoretical framework to investigate when and how engaging in social loafing enhances one’s job performance. Drawing on the effort-recovery model and moral cleansing theory, we propose that social loafing may improve subsequent job performance by enhancing recovery and guilt. Specifically, we argue that among employees who experience higher job demands or have higher moral identity, social loafing in the morning enhances their job performance in the afternoon by facilitating recovery or guilt in the morning. Two-wave daily data collected across ten consecutive workdays using the experience sampling method (ESM) supports this model. We discuss how this research identifies a functional basis for social loafing and provides implications for research and practice.